The Influence of Business Capital, Accounting Knowledge, and E-Commerce Use on the Sustainability of MSMEs in Bantul Regency (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy, especially in Bantul Regency, where they significantly contribute to the Gross Regional Product(GRDP) and job creation. Despite a rise in MSMEs numbers from 2021 to 2024, their long-term viability is hindered by issues like insufficient funding, inadequate accounting skills, and underutilization of e-commerce platforms. This research investigates how businesses, accounting knowledge, and e-commerce adoption impact MSME sustainability in Bantul Regency. Employing a quantitative method, it collected primary data via questionnaires from 100 MSME operators selected through purposive sampling. Analysis involved multiple linear regression. Findings indicated that business capital had no significant influence on sustainability, while accounting knowledge and e-commerce use positively and significantly boosted it. The R2 value of 29% show that these factors collectively explain 29% of MSME sustainability variance, with the remaining 71% attributed to external variables. The study highlights the need to enchane accounting education and digital tools to boost MSME competitiveness and resilience.